Un modele cognitif de structures discursives - son application a l’enseignement / l’apprentissage de langues etrangeres - Miczka, Ewa (Neophilologica, 2004)
The article discusses connections between concepts of foreign language teaching and the development of linguistic models of textual units bigger than one phrase. It contains a synthesis of the 20,h c. models of text and discourse with some special attention paid to the issue of coherence. Still, the main part of the article is devoted to a description of the evolution of contemporary methods used in foreign language teaching, which occurred under the influence of cognitive linguistics.